Back-to-back correlations for finite expanding fireballs - Padula, S. S.; Krein, G.; Csorgo, T.; Hama, Y.; Panda, P. K. (American Physical Soc, 2006)
Back-to-back correlations of particle-antiparticle pairs are related to the in-medium mass-modification and squeezing of the quanta involved. They are predicted to appear when hot and dense hadronic matter is formed in high energy nucleus-nucleus collisions. The survival and magnitude of the back-to-back correlations (BBC) of boson-antiboson pairs generated by in-medium mass modifications are studied here in the case of a thermalized, finite-sized, spherically symmetric expanding medium. We show that the BBC signal indeed survives the finite-time emission, as well as the expansion and flow effects, with sufficient intensity to be observed at BNL Relativistic Heavy Ion Collider (RHIC).